2021
DOI: 10.1113/ep088657
|View full text |Cite
|
Sign up to set email alerts
|

The influence of increased venous return on right ventricular dyssynchrony during acute and sustained hypoxaemia

Abstract: Regional heterogeneity in timing of right ventricular (RV) contraction (RV dyssynchrony; RVD) occurs when pulmonary artery systolic pressure (PASP) is increased during acute hypoxia. Interestingly, RVD is not observed during exercise, a stimulus that increases both PASP and venous return. Therefore, we hypothesised that RVD in healthy humans is sensitive to changes in venous return, and examined whether (i) increasing venous return in acute hypoxia lowers RVD and (ii) if RVD is further exaggerated in sustained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(27 citation statements)
references
References 43 publications
(89 reference statements)
1
26
0
Order By: Relevance
“…Twelve studies explored effects of simulated altitude and included a total of 199 healthy adults (Huez et al, 2005 ; Kjaergaard et al, 2007 ; Reichenberger et al, 2007 ; Hanaoka et al, 2011 ; Pavelescu and Naeije, 2012 ; Boos et al, 2013 , 2016 ; Goebel et al, 2013 ; Netzer et al, 2017 ; Seccombe et al, 2017 ; Pezzuto et al, 2018 ; Ewalts et al, 2021 ). Study participants were exposed to various degrees of hypoxia from 9.9 to 12.5% fraction of inspired oxygen (FiO 2 ), which correspond to altitude levels ranging from 4,000 to 5,500 m. Altitude was simulated by either hypobaric or normobaric hypoxic chamber exposure or hypoxia breathing.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twelve studies explored effects of simulated altitude and included a total of 199 healthy adults (Huez et al, 2005 ; Kjaergaard et al, 2007 ; Reichenberger et al, 2007 ; Hanaoka et al, 2011 ; Pavelescu and Naeije, 2012 ; Boos et al, 2013 , 2016 ; Goebel et al, 2013 ; Netzer et al, 2017 ; Seccombe et al, 2017 ; Pezzuto et al, 2018 ; Ewalts et al, 2021 ). Study participants were exposed to various degrees of hypoxia from 9.9 to 12.5% fraction of inspired oxygen (FiO 2 ), which correspond to altitude levels ranging from 4,000 to 5,500 m. Altitude was simulated by either hypobaric or normobaric hypoxic chamber exposure or hypoxia breathing.…”
Section: Resultsmentioning
confidence: 99%
“…RV-S′ values remained unchanged in 4 studies (Huez et al, 2005 ; Kjaergaard et al, 2007 ; Pavelescu and Naeije, 2012 ; Pezzuto et al, 2018 ) and were increased in one study (Boos et al, 2013 ) or decreased in another study after 1 h hypoxia exposure (Netzer et al, 2017 ). RV-GLS was evaluated in 2 studies and showed opposite results (Goebel et al, 2013 ; Ewalts et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations